What evidence exists on the application of biocultural approaches within infectious disease research from low- and middle-income countries? A scoping review of the peer-reviewed literature - Emmanuel S. Tomude; Bethan V. Purse; Sarah J. Burthe; Juliette C. Young; Festus A. Asaaga (Social Sciences and Humanities Open)
There is increasing research interest in bio or socio-cultural approaches in the context of infectious disease challenges, predicated on the notion that addressing health inequities in poor and marginalised populations requires nuanced, place-based understanding of the burden and impacts of health problems and associated factors determining health status and outcomes. Yet, to date, there is no systematic synthesis of how extant studies have used a biocultural approach to characterise social vulnerability in the context of zoonoses affecting humans, especially in low-and middle-income countries (LMICs). We conducted a scoping review of the scientific literature that have applied biocultural approaches within zoonoses research from LMICs. In total 43 studies were reviewed mostly from Africa (n = 24), followed by Asia (n = 12) and Latin America (n = 1). Ebola virus disease (n = 13) was the topmost disease of research interest, with reported studies mostly led by authors affiliated to Global North higher education institutions (particularly in the USA). Overall, the review showed that place-based differences and cultural systems are important determinants of vulnerability to many reported disease hazards across LMIC settings. Biocultural approaches are not holistically considered within zoonoses research and largely inclined towards the ‘cultural’ (n = 38) relative to the ‘biological’ (n = 5) aspect that influenced place-based resource use and health decision-making. The top three biocultural categories used were: livelihood practices, beliefs and knowledge systems. Twenty-five social vulnerability indicators (categorised into 6 components) were identified of which at-risk population demography (e.g. children, % of adults), education and socioeconomic status were commonly reported. Altogether, the review highlights the untapped potential of bio-culturally-informed research in advancing granular, place-based understanding of the complex socioecological, political and cultural factors that can lead to differences in disease vulnerabilities and capacities of different populations to adapt.